PAKISTAN: Media, politics and the threats to journalists in Pakistan - Rukhsana Aslam (Asia Pacific Network, 2015)
This article examines how the fundamental right of freedom of expression for news media in Pakistan continues to be threatened both by the government and conflicting parties, an issue that is compounded by the threat to the journalists’ safety and survival. Giving examples of three Pakistani journalists who lost their lives after their investigations during the America’s so called ‘War on Terror’, the article gives an account of the nature of the dangers and threats that are faced by the journalists in Pakistan who report on armed political conflicts. Drawing on the experiences of five other journalists, who were interviewed during research visits to Pakistan in 2012 and 2014, the author also reflects on the role of journalists in the light of the social responsibility theory and explores some of the factors that contribute towards making conflict reporting a dangerous business in Pakistan. Pictured: Figure 1: The Press in Stress report in 2012. Shown in the cover image is a curbside radio-seller in Quetta. FM radio is hugely popular in Balochistan. Image: Aurangzazib Khan